2013
DOI: 10.1089/jmf.2011.0326
|View full text |Cite
|
Sign up to set email alerts
|

Gas Chromatography–Mass Spectrometry Confirmation of the Sensory Scent Features of the Most Commonly Consumed Agaricus bisporus and Agaricus subrufescens Exhibiting Anticancerous Traits

Abstract: In Hungary, fairly little is known about Agaricus subrufescens Peck (formerly called Agaricus blazei Murrill), which is cultivated on an industrial scale in the Far East. Nevertheless, this mushroom species exerts a curative influence and might become a new pillar of cancer research and antitumorous therapy. The present study gives a detailed discussion on the compositional differences of the scent components of A. subrufescens and its close relative Agaricus bisporus based on gas chromatography-mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“… Consequently, compound U6 could be identified as drimenol linoleic acid ester, and a good match for reported GC/MS data for drimenol esters isolated from mushrooms was achieved (Figure S4). Fatty acid esters of drimenol and other sesquiterpenes have been reported in Lactarius mushrooms and are thought to be involved in chemical defense upon cell injury. , Recently, Muñoz et al reported drimenol as a constituent of Drymis winteri leaves, and Györfi et al detected free drimenol as a major compound in the volatile fraction of A. bisporus . , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Consequently, compound U6 could be identified as drimenol linoleic acid ester, and a good match for reported GC/MS data for drimenol esters isolated from mushrooms was achieved (Figure S4). Fatty acid esters of drimenol and other sesquiterpenes have been reported in Lactarius mushrooms and are thought to be involved in chemical defense upon cell injury. , Recently, Muñoz et al reported drimenol as a constituent of Drymis winteri leaves, and Györfi et al detected free drimenol as a major compound in the volatile fraction of A. bisporus . , …”
Section: Resultsmentioning
confidence: 99%
“…33,34 Recently, Munõz et al reported drimenol as a constituent of Drymis winteri leaves, and Gyorfi et al detected free drimenol as a major compound in the volatile fraction of A. bisporus. 35,36 Changes in the Lipid Composition Detected by MALDI-TOF-MS. MALDI-TOF-MS spectra of both identically prepared samples were not fully identical (Figure S6), which was most likely due to natural differences between individual mushrooms. Nevertheless, these differences were small compared to the more distinct differences between samples processed with methods L1 and L2 (Figure 3).…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%